Phosphatase and tensin homolog (PTEN) is down-regulated in human NK/T-cell lymphoma and corrects with clinical outcomes. Issue 29 (July 2017) - Fu, Xiaorui; Zhang, Xudong; Gao, Jinli; Li, Xin; Zhang, Lei; Li, Ling; Wang, Xinhua; Sun, Zhenchang; Li, Zhaoming; Chang, Yu; Chen, Qingjiang; Zhang, Mingzhi
Abstract : Abstract: Nasal-type natural killer/T-cell (NK/T-cell) lymphoma is a more aggressive sub-group of non-Hodgkin lymphoma, which is more common in Asia. The phosphatase and tensin homolog ( PTEN ) was originally discovered as a candidate tumor suppressor mutated and lost in various cancers. However, its clinical value and role in NK/T-cell lymphoma remain to be further explored. In the present study, we analyzed PTEN protein expression in 60 cases of human NK/T-cell lymphoma tissues and 40 cases of control nasal mucosa tissues specimens by immunohistochemical analysis. As a result, positive rate of PTEN protein expression in NK/T-cell lymphoma tissues (33.3%) is significantly lower than that of control nasal mucosa tissues (85.0%) ( P < .01). However, no significant association was found between PTEN protein expression and sex, age, tumor location, clinical staging (Ann Arbor staging), or serum lactate dehydrogenase level ( P > .05). Instead, PTEN protein was inversely corrected with Ki-67 expression, indicating a functional role in PTEN in human NK/T-cell lymphoma ( P < .05). For clinical outcomes, PTEN positive rate significantly increased in objective response group (CR+PR) (43.5%) compared with SD+PD group (18.9%). Furthermore, overexpression of PTEN contributed to chemotherapy sensitivity to different doses of cisplatin (DDP) in human NK/T-cell lymphoma SNK-6 cells. These results suggest that PTEN may regulate chemotherapy sensitivity of NK/T-cell lymphoma and contribute to clinical outcomes. These findings indicate PTEN to be a potential target anti-tumor therapeutics for NK/T-cell lymphoma. Abstract : Supplemental Digital Content is available in the text